Widowhood and Mortality Among Chinese Older Adults in Singapore: The Roles of Gender and Perceived Social Support. (27th October 2022) - Barrenetxea, Jon; Feng, Qiushi; Gu, Danan; Koh, Woon-Puay
Abstract: Objectives: Although the association between widowhood and mortality is well established, the impact of widowhood on mortality could differ by social support, gender, and widowhood duration. We studied the association between widowhood and mortality among older Chinese adults in Singapore and analyzed how social support, gender, and widowhood duration may modify this association. Methods: We used data from 15, 858 participants aged 61–96 years from the third follow-up of the population-based Singapore Chinese Health Study in 2014–2016. Mortality data were obtained through linkage with the national death registry through 31 st December 2018, and social support was measured with the Duke Social Support Scale. We used Cox proportional hazard models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for the association between widowhood and mortality risk. Results: Compared with those married, widowed adults had a higher mortality risk (HR = 1.18, 95% CI = 1.01–1.38), and this risk was higher for those who were either recently widowed (<5 years; HR = 1.28, 95% CI = 1.00–1.63) or long-term widowed (>10 years; HR = 1.27, 95% CI = 1.07–1.54). Among men, those recently widowed had the highest mortality risk (HR = 1.50, 95% CI = 1.06–2.13), whereas, among women, those long-term widowed had the highest mortality risk (HR = 1.26, 95% CI = 0.99–1.60). In the analysis stratified by social support, widowhood was associated with mortality among those with low social support (HR = 1.27, 95% CI = 1.05–1.54), but not among those with high social support (HR = 1.01, 95% CI = 0.76–1.33). Discussion: Widowhood was associated with increased mortality risk, particularly among recently widowed men and long-term widowed women. Having adequate social support could attenuate the adverse effects of widowhood among older adults.